Co-occurring cyber and in-person victimisation of bullying and sexual harassment: the associations to depressive symptoms in Swedish adolescents - Albin Dahlström; Heléne Dahlqvist; Katja Gillander Gådin (BMC Public Health)
Abstract Background Poor mental health has increased among adolescents in recent decades. Bullying and sexual harassment, both cyber and in-person, are each associated with increased depressive symptoms in adolescents and being victimised by co-occurring types is more common than just one single type of victimisation. The study aimed to investigate the association between co-occurring victimisation and depressive symptoms in adolescents when controlling for screen time, social support, physical activity, and personal relative affluence. Method Cross-sectional survey data from 1211 respondents (50.1% girls) aged 15–16 were used to conduct modified Poisson regression with robust error variance analyses for girls and boys separately. Four scales were used to measure cyber and in-person bullying and sexual harassment, and CESD-R10 was used to measure depressive symptoms. Results About 47% of girls and 20% of boys experienced all four types of victimisation, and about 12% of girls and 25% of boys experienced none of them. When controlled for all included variables, all number of victimisation types of bullying and/or sexual harassment were associated with depressive symptoms in girls. In comparison, only four types of victimisation were associated with depressive symptoms in boys. Conclusions The study showed that co-occurring victimisation was associated with depressive symptoms even after controlling for other relevant factors in both genders. However, in girls, all numbers of victimisation were associated with depressive symptoms.